Nanowires embedded porous TiO2@C nanocomposite anodes for enhanced stable lithium and sodium ion battery performance. Issue 7 (May 2020) - Wang, Yu; Li, Na; Hou, Chuanxin; He, Biao; Li, Jiajia; Dang, Feng; Wang, Jun; Fan, Yuqi
Abstract: A porous carbon nanocomposite with embedded TiO2 nanowires (NWs) was synthesized using a two-step synthetic method in which carbon matrix was obtained by carbonizing a vacuum dried gel. This unique structure in which TiO2 nanowires uniformly distributed in and tightly bonded to the carbon matrix shortened the electron transport path and reduced the transmission resistance. Nanoporous structure ensured continuous transfer of Li + /Na + and supplied a large specific surface area of 280.82 m 2 g −1 to provide more active sites. Different from other existing works on TiO2 @C anode materials with TiO2 loading higher than 60 wt%, the obtained very small amount of TiO2 ( 12 wt%) improved the electrochemical and long-cycle performance of carbon substrate with TiO2 NWs embedded significantly, due to uniformly distributed TiO2 NWs throughout the carbon matrix. These TiO2 @C composite anodes could deliver a specific capacity of 286 mA h g −1 at 0.3 C, 197 mA h g −1 at 0.15 C for lithium and sodium ion batteries, respectively. It maintained remarkably stable reversible capacities of 128 and 125 mA h g −1 for lithium and sodium ion batteries at 3 C during 2500 cycles, respectively. Smaller fluctuations and smoother curves demonstrated that sodium ion storage was more stable than lithium ion storage for the TiO2 @C composite anode. In addition, the capacitive contributions of TiO2 @C in both systems are quantified by kinetics analysis.